Kinetics of Cytokines and Anti-SARS-CoV-2 Spike Glycoprotein S1 IgM and IgG1 in COVID-19 Infected Patients in Togo - Katawa, Gnatoulma; Halatoko, Wemboo; Koba, Adjaho K.; Tchopba, Christèle Nguepou; Tchadie, Edlom P.; Simfele, Hombamane C.; Amessoudji, Oukoe M.; Adjobimey, Tomabu; Ritter, Manuel; Dorkenoo, Ameyo M.; Kolou, Malewe (My University, 2024)
Background: COVID-19, caused by, had spread throughout the world. Its clinical manifestations ranged from asymptomatic to severe forms. The immunological markers that determine these forms are poorly investigated in Togo. This study aimed to investigate the dynamics of antibodies and cytokines in COVID-19 infected patients in Togo. Methodology: Sera from symptomatic (n = 40) and asymptomatic (n = 40) patients, collected at Day0, Day3 and Day10 post admission, were analyzed for SARS-CoV-2 specific IgM and IgG1 antibodies and IL-1b, IL-6, TNFa, IL-5, IL-10, IL-17A and IFNg by sandwich ELISA. Results: In response to SARS-CoV-2 infection, IgM was expressed first followed by IgG1 in symptomatic patients. However, in asymptomatic patients, these antibodies were expressed simultaneously from the beginning of the infection with higher titers of IgG1. Except of IL-1b that increased from the admission to D10 all other cytokines were elevated at the admission and decreased to D10. Serum IL-6 levels were three times higher in symptomatic compared to asymptomatic patients. Conclusion: COVID-19 asymptomatic patients were characterized by high IgG1 antibodies titers whereas COVID-19 symptomatic patients, by high IL-6 levels.
Keywords: COVID-19; Antibodies; Cytokines; IgM; IgG; Togo